1993
DOI: 10.1007/bf02598282
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in cardiovascular medication taking

Abstract: Major treatment gaps occur frequently, even in carefully selected ambulatory populations, and generally escape detection. The compliance patterns and gaps may contribute to reported excesses of cardiovascular morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…However, previous research has not found consistent factors that predict adherence. 15,16 Our study also determined that age was a significant predictor of adherence, with older age predicting better adherence. Notably, however, our study lacks the extreme category of elderly, therefore, the association of greater age and better adherence may not hold for those older than 70 years.…”
Section: Discussionmentioning
confidence: 96%
“…However, previous research has not found consistent factors that predict adherence. 15,16 Our study also determined that age was a significant predictor of adherence, with older age predicting better adherence. Notably, however, our study lacks the extreme category of elderly, therefore, the association of greater age and better adherence may not hold for those older than 70 years.…”
Section: Discussionmentioning
confidence: 96%
“…Several methods have been used to assess the degree of adherence to treatment, including self-report measures, direct pill counts, electronic monitoring of pill counts (bottle opening electronic recordings) and biological methods [12]. All of them are imperfect and tend to overestimate treatment compliance [13][14][15][16][17][18][19]. Direct pill counts can identify adherence problems when bottles with an excessive number of pills are returned, but participants may discard drugs and return empty containers.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 41 actual articles, the disease states were as follows: HIV (n = 18; 43.9%), [11][12][13][14][15][16][17][18]20,26,28,31,33,[35][36][37]43,44] psychotic disorders (n = 4; 9.8%), [29,34,41,49] cardiovascular diseases (n = 3; 7.3%), [32,38,50] hypertension (n = 3; 7.3%), [23,24,27] transplant (n = 2; 4.9%) [21,30] and diabetes mellitus (n = 2; 4.9%). [19,46] The sample sizes ranged from 5 to 1021 (median = 61).…”
Section: Study Characteristicsmentioning
confidence: 99%